Taking hospital pathogen surveillance to the next level. Issue 4 (26th April 2023) - Werner, Guido; Couto, Natacha; Feil, Edward J.; Novais, Angela; Hegstad, Kristin; Howden, Benjamin P.; Friedrich, Alexander W.; Reuter, Sandra
Abstract : High-throughput bacterial genomic sequencing and subsequent analyses can produce large volumes of high-quality data rapidly. Advances in sequencing technology, with commensurate developments in bioinformatics, have increased the speed and efficiency with which it is possible to apply genomics to outbreak analysis and broader public health surveillance. This approach has been focused on targeted pathogenic taxa, such as Mycobacteria, and diseases corresponding to different modes of transmission, including food-and-water-borne diseases (FWDs) and sexually transmitted infections (STIs). In addition, major healthcare-associated pathogens such as methicillin-resistant Staphylococcus aureus, vancomycin-resistant enterococci and carbapenemase-producing Klebsiella pneumoniae are the focus of research projects and initiatives to understand transmission dynamics and temporal trends on both local and global scales. Here, we discuss current and future public health priorities relating to genome-based surveillance of major healthcare-associated pathogens. We highlight the specific challenges for the surveillance of healthcare-associated infections (HAIs), and how recent technical advances might be deployed most effectively to mitigate the increasing public health burden they cause.